Extrapolation suitability index for sustainable vegetable cultivation in Babati district, Tanzania - Muthoni, Francis Kamau; Delore, Jean Marc; Lukumay, Philipo J.; Ochieng, Justus (Frontiers in Sustainable Food Systems, 2023)
Land suitability assessment matches crop requirements with available resources to promote sustainable production. Scaling out of sustainable agricultural intensification practices to suitable biophysical and socio-economic conditions reduces the risk of failure and increases their adoption rate. This study applies a geospatial framework to identify potentially suitable sites for extrapolating two improved vegetable cultivars grown under integrated management practices (IMP’s) in Babati District of Tanzania. On-farm trial data on the yield and income of two cultivars were used as a reference. Extrapolation was based on the gridded biophysical and socio-economic layers that limit the production of the two improved vegetable cultivars' productivity. The extrapolation suitability index (ESI) for the two cultivars showed the areas where cultivation of the two improved vegetable cultivars under IMP’s can be scaled-out with a potentially low risk of failure. We generate maps of the most important limiting factor in every pixel for each cultivar in every pixel to guide the spatial targeting of appropriate remedial measures. Application of these maps will promote evidence-based scaling out of improved vegetable technologies by the extension and development agencies.